First records of six ant species (Hymenoptera: Formicidae) for Slovenia - Gregor Bračko; Lucija Česnik (Natura Sloveniae)
Six ant species recorded for the first time in Slovenia are presented: Camponotus gestroi, Hypoponera eduardi, Lasius lasioides, Tapinoma cf. nigerrimum, Temnothorax jailensis and Temnothorax turcicus. They were found in the period of the last 9 years, five of them in southwestern Slovenia in the Submediterranean region, while T. turcicus was recorded in northeastern Slovenia. Findings of C. gestroi and T. jailensis considerably extend their previously known ranges in Europe.